Sport classification for athletes with visual impairment and its relation with swimming performance - Elaine Cappellazzo Souto; Leonardo dos Santos Oliveira; Claudemir da Silva Santos; Márcia Greguol (Universidade Federal de Santa Catarina, 2017)
The medical classification (MC) adopted for swimmers with vision visual impairment (VI) does not clearly elucidate the influence of vision loss on performance. In a documentary research, the final time in the 50-, 100- and 400-m freestyle events and MC (S11, S12 and S13) of national (n = 40) and international (n = 72) elite swimmers was analyzed. The analysis was performed using the Kruskal-Wallis test and Spearman's correlation with 95% confidence (P < 0.05) and Cohen's d was calculated. There was a large effect of MC on the final time in the 50-m (P = 0.034, d = 1.55) for national athletes and in the 50-m (P = 0.001, d = 2.64), 100-m (P = 0.001, d = 3.01) and 400-m (P = 0.001, d = 2.88) for international athletes. S12 and S13 classes were faster compared to S11 class for all international events, but only in the 50-m for the national event (P < 0.05). It was found a strong negative relationship between the final time and MC for international athletes (Spearman's Rho ≥ 0.78). There was a significant influence of MC on the performance of swimmers in freestyle races, especially in international swimmers. Thus, having a visual residue seems to be sufficient for S12 and S13 swimmers to achieve similar performance.